2008
DOI: 10.1136/vr.162.6.177
|View full text |Cite
|
Sign up to set email alerts
|

Equine parascarosis under the tropical weather conditions of Ethiopia: a coprological and postmortem study

Abstract: A cross-sectional coprological survey in the regions of Ada, Akaki, Bereh and Boset, and a retrospective postmortem investigation were conducted to study the epidemiology of Parascaris equorum in donkeys and horses in Ethiopia. Faecal samples from 803 working donkeys and 402 horses were collected, and the numbers of worms recovered from 112 donkeys examined postmortem between 1995 and 2004 were analysed. There was a high prevalence of infection and faecal egg output of P equorum in both donkeys and horses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
2
13
2
Order By: Relevance
“…This result is higher than the prevalence reported in Ethiopia by Yoseph et al [29], Fikru et al [11], Getachew et al [30] who reported 15.7%, 7.3%, and 16.2%, respectively and in Lesotho by Melissa et al [28] who reported 21.6% in horses. The prevalence of Parascaris equorum was 42.29% in donkeys in the present study is higher than 15.7% and 17.3% reported by Yoseph et al [21] and Fikru et al [11] in donkeys.…”
Section: Discussioncontrasting
confidence: 55%
“…This result is higher than the prevalence reported in Ethiopia by Yoseph et al [29], Fikru et al [11], Getachew et al [30] who reported 15.7%, 7.3%, and 16.2%, respectively and in Lesotho by Melissa et al [28] who reported 21.6% in horses. The prevalence of Parascaris equorum was 42.29% in donkeys in the present study is higher than 15.7% and 17.3% reported by Yoseph et al [21] and Fikru et al [11] in donkeys.…”
Section: Discussioncontrasting
confidence: 55%
“…The high prevalence of P. equorum irrespective of the age of the donkeys is consistent with the finding of Wells et al (1998) and Getachew et al (2008b). This is in disagreement with the general opinion that P. equorum is a parasite of young horses (Clayton and Duncan 1979).…”
Section: Gasterophilus Intestinalissupporting
confidence: 62%
“…For developing countries, reports are somewhat conflicting. In Ethiopia, Fikru et al (2005) and Gebreab (1998) both reported increased prevalence in 'younger animals', whereas Getachew and colleagues did not find associations between P. equorum infection and age in either horses (Getachew et al 2008a) or donkeys (Getachew et al 2010). The findings in Lesotho of no age association with infection prevalence appear to concur with the latter studies and raise the question as to why the pattern of infection appears to differ between equids in developed and developing countries.…”
Section: Discussionmentioning
confidence: 55%
“…Fikru et al (2005) reported prevalence at 17.1% in the Ethiopian highlands and (Getachew et al 2008a) reported prevalence in horses of 16.2%. Reported prevalence in donkeys in four sites in Ethiopia are higher at 43.5% (Gebreab 1998), 50% (Ayele 2006), 51.1% (Getachew et al 2008a) and 51% (Getachew et al 2010). The higher prevalence in donkeys may be due to differences in population age structures between the species or to species differences in immune response to endoparasite infestation.…”
Section: Discussionmentioning
confidence: 95%